Upaya Meningkatkan Minat Dan Hasil Belajar Matematika Siswa Menggunakan Metode Inquiri Terbimbing Di MTs. Al-Ishlahussibyan - Dewi, Ekawati; Masjudin, Masjudin; Abidin, Zainal (Media Pendidikan Matematika, 2023)
The problem that often occurs is the decreased interest in learning and the results of learning mathematics in these students. The purpose of this study was to increase students’ interest and learning outcomes in mathematics using the guided inquiry method at MTs. Al-Ishlahussibyan. This type of research is classroom action research which consists of two cycles, each cycle consisting of several stages including the stages of planning, action, implementation and reflection on the results of the research conducted. The population of this research is all MTs students. Al-Ishlahussibyan, with the sample of this study being class IX students, data collection was carried out by administering an evaluation test of students’ mathematics learning outcomes and a questionnaire of students’ interest in learning mathematics, the results showed that there was an increase in the average learning outcomes of 57.98 out of 28, 77 in Cycle I and became 86.75 in Cycle II, as well as increasing students’ interest in learning mathematics from cycle I with a positive category to Cycle II becoming a very positive category, it can be concluded that the use of the guided inquiry method can increase students’ interest and learning outcomes in mathematics in class IX at MTs. Al-Ishlahussibyan. Based on this research, it is hoped that it can help students and teachers in the learning process so that it can increase students’ interest and learning outcomes in mathematics for the better.